Illustrated Genesis in Hebrew - McNinch, Timothy; Neely, Keith, 1943- (GlossaHouse; Wilmore, NY., 2016)
The Hebrew text of the Book of Genesis is set within colorful illustrations to represent narration, dialogue, monologue, and scripture quotations, together with a new English version by GlossaHouse translators.
Text in Hebrew and English.
Keywords: Bible. -- Comic books, strips, etc; Bible. Genesis -- Cartoons and comics; Bible. Genesis -- Picture Bible